Statistical Analysis of Urbanisation Sustainability in The European Union Countries - Joanna PERZYŃSKA (Communications of International Proceedings, 2021)
The article presents the issue of urbanisation as a challenge to the achievement of Sustainable Development Goals. The empirical study evaluates the level of urbanisation sustainability and its changes in 28 European Union Member States in 2012 and 2018. The research data from the EU SDGs indicators set provided by Eurostat was used. Sustainable urbanisation is a multidimensional phenomenon that can be characterised by many variables. Therefore, the study applied the method of multivariate statistical analysis, the TOPSIS procedure. As a result, a synthetic measure was determined, which made it possible to construct rankings of countries and their classes that are typological groups with a similar level of urbanisation sustainability. The study showed the existence of diversification among the studied countries. The first place in the ranking, i.e. the highest level of urbanisation sustainability due to the variables considered in the study, was held by Spain in 2012 and by Austria in 2018. In both years, Latvia was ranked last. The biggest advance in the ranking was for Slovakia and the biggest fall was for the United Kingdom. The class with the highest level of urbanisation sustainability included Austria and Ireland in both years, in 2012 additionally Spain, Germany, Denmark, Belgium and Luxembourg and in 2018 only Czechia. The class with the lowest level of urbanisation sustainability included Greece, Romania, Bulgaria and Latvia in both years, and in 2018 was joined by Sweden and Cyprus.
Keywords: Multivariate Statistical Analysis; Sustainable Development Goals; TOPSIS Procedure; Urbanisation.